Assessing the undergraduate medical students’ acceptance and barriers of community-based education in population and Puskesmas levels: A preliminary study - Pradnya, Matilda Stella; Sebong, Perigrinus H (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify aspects of acceptance and barriers to implementing community-based education (CBE) at the population and Puskesmas levels. Methods: A preliminary study was conducted in the Faculty of Medicine, Soegijapranata Catholic University, Semarang, in April 2024. Data were collected using a Likert-scale questionnaire, which surveyed 95 medical students participating in the CBE program at both the population and Puskesmas settings. Data analysis was carried out descriptively. Results: The distribution of respondents' experiential learning perceptions from the category "good" was a majority in the cycle of concrete experience aspect (100% at the population level and 89,58% at the Puskesmas level) and reflective observation (100% at the population level and 87,5% at the Puskesmas level). However, the percentage of 'disagree' and 'strongly disagree' ratings was found to be more frequent in Puskesmas when it came to accepting CBE benefits for students. Conclusion: Students benefit from the overall implementation of CBE at the population and Puskesmas levels. Further action research is needed to accommodate student learning styles in community-based education programs.